Emergent Dynamics of a Macroeconomic Agent Based Model with Capital and Credit - Tiziana Assenza; Domenico Delli Gatti; Jakob Grazzini (Center for Economic Studies and ifo Institute (CESifo), 2014)
Building on the framework put forward by Delli Gatti et al. 2011, in this paper we present and discuss a Macroeconomic Agent-Based Model with Capital and Credit (hereafter CC-MABM). The novelty of this model with respect to the previous framework consists in the introduction of capital goods that firms producing consumption goods (C-firms) purchase from capital goods producers (K-firms). The introduction of durability (in the form of capital which depreciates gradually) has important consequences for the emergent macrodynamic behavior. The present CC-MABM is essentially a two-sector macro ABM. In a stylized supply chain the upstream sector, consisting of firms producing capital goods (K-firms) supply a durable and sticky input (capital) to the downstream sector consisting of firms producing consumption goods (C-firms) to be sold to households. Both C-firms and K-firms resort to bank loans to satisfy their financing needs. There are two-ways feedbacks between markets and sectors which yield interesting emerging properties at the macro level.
Keywords: E32; 330; agent-based macroeconomics; capital; credit; crisis; upstream; down-stream